2023
DOI: 10.3389/fbioe.2023.1173381
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity focused ultrasound targeted microbubble destruction reduces tumor blood supply and sensitizes anti-PD-L1 immunotherapy

Abstract: Immune checkpoint blockade (ICB) typified by anti-PD-1/PD-L1 antibodies as a revolutionary treatment for solid malignancies has been limited to a subset of patients due to poor immunogenicity and inadequate T cell infiltration. Unfortunately, no effective strategies combined with ICB therapy are available to overcome low therapeutic efficiency and severe side effects. Ultrasound-targeted microbubble destruction (UTMD) is an effective and safe technique holding the promise to decrease tumor blood perfusion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…This resulted in several complete responders compared to (chemo)immunotherapy alone, demonstrating the effectiveness of ablative UTMC treatment in cancer therapy [ 176 ]. Ablative UTMC was employed to explore immunogenic cell death in a TNBC model (4T1, immune excluded with low TMB); UTMC induced the translocation and expression of calreticulin and enhanced IL-12 and TNF-α, leading to increased infiltration of DC and CTL in both the tumor and TDLNs [ 177 ].…”
Section: Immune Profiles Fus Bioeffects and Icimentioning
confidence: 99%
“…This resulted in several complete responders compared to (chemo)immunotherapy alone, demonstrating the effectiveness of ablative UTMC treatment in cancer therapy [ 176 ]. Ablative UTMC was employed to explore immunogenic cell death in a TNBC model (4T1, immune excluded with low TMB); UTMC induced the translocation and expression of calreticulin and enhanced IL-12 and TNF-α, leading to increased infiltration of DC and CTL in both the tumor and TDLNs [ 177 ].…”
Section: Immune Profiles Fus Bioeffects and Icimentioning
confidence: 99%
“…By combining ultrasound with tumor targeting microbubbles, Hu J team showed that USNB promoted the infiltration and antitumor activity of CD8 + T cells ( Sun et al, 2023 ). In addition, studies have shown that the new combination therapy of low intensity focused ultrasound targeted microbubble destruction (LIFU-TMD) and PD-L 1 blockade also shows the same effect of reducing tumor and enhancing T cell infiltration ( Wu N. et al, 2023 ). Furthermore, in order to improve the cure rate of solid tumor based on immune adjuvant, some tumor-associated antigens (TAAs) produced by experimental UMC therapy show vaccine activity, especially in the presence of immune adjuvant, which jointly promoted the maturation of dendritic cells and induced the production of cytokines ( Zhang N. et al, 2021 ).…”
Section: Mechanism and Application Of Ultrasound Combined With Microb...mentioning
confidence: 99%
“…In addition, the ultrasonic cavitation effect exhausted tumor blood perfusion through abnormal blood vessel rupture, induced TME to transform and sensitize anti-PD-l immunotherapy, induced some cellular immunogenic cell death (ICD), and significantly inhibits the growth of mouse 4T1 breast cancer. Moreover, it was also found that the levels of dendritic cells (DCs) and CD8 + T cells in tumor tissues increased significantly ( Wu N. et al, 2023 ). More than that, UTMD and small molecule ribonucleic acid have the potential to interfere with the immune system.…”
Section: Regulation Of Tumor Immune Microenvironment By Utmdmentioning
confidence: 99%
“…Wu et al divided breast tumours (4T1) into the following treatment groups: untreated, US-only, CA-only, and US+CA [ 43 ]. They detected a significantly ( p < 0.05) higher (1.2–1.5-fold) expression of HMGB1 and a significantly ( p < 0.05) lower ATP level in vitro after US+CA treatment compared to the three other groups and reported an increase in calreticulin expression in the US+CA group in vivo, indicative of DAMP release.…”
Section: Cavitation-mediated Immunomodulationmentioning
confidence: 99%
“…They detected a significantly ( p < 0.05) higher (1.2–1.5-fold) expression of HMGB1 and a significantly ( p < 0.05) lower ATP level in vitro after US+CA treatment compared to the three other groups and reported an increase in calreticulin expression in the US+CA group in vivo, indicative of DAMP release. A significant ( p < 0.01 and p < 0.05, respectively) increase in IL-12 and Tumour necrosis factor alpha (TNF- ) levels was also reported [ 43 ].…”
Section: Cavitation-mediated Immunomodulationmentioning
confidence: 99%